BILINGUAL SEL DEVELOPMENT AS AN EMERGING INTERDISCIPLINARY FRAMEWORK IN CONTEMPORARY BILINGUAL PEDAGOGY - Buchkovska, Valeriia (Global Prosperity, 2026)
The article examines the systemic crisis within the U.S. educational landscape associated with the inefficiency of traditional linguocentric bilingual instruction models (TBE, DLI, ESL). The author substantiates the "Bilingual SEL Development" methodology as an interdisciplinary framework, wherein socialization and emotional development (SEL) become the psycho-pedagogical basis of the general language acquisition process. The work takes a close look at how emotional intelligence can be woven into the way language is actually used and taught, specifically through a socio-affective modulation algorithm and what the authors call an emotional scaffolding system. Early data collected from a pilot run at Smartik Kids Learning Center offer some encouraging signs: students showed real gains in bilingual communication, were more willing to speak up in class, which suggests lower language anxiety, and seemed to settle into academic life faster than expected. The study looks at how AI-based tools are used in practice, how families are involved, and what can be learned from a bilingual program in Hawaii. It treats generative AI as a supporting tool, with clear benefits but also clear limits. In all these cases, technology stays in a secondary role. For bilingual learners, progress depends more on stable support, trusting relationships, and emotional readiness than on the tools themselves.